The influence of brand awareness, brand associations, perceived quality, and brand loyalty towards brand equity of Legoland Malaysia / Mira Elliana Zainal - Zainal, Mira Elliana (Faculty of Business and Management, 2015)
The purpose of this research is to study the influence of brand awareness, brand associations, perceived quality and brand loyalty towards brand equity of LEGOLAND Malaysia. LEGOLAND Malaysia faces new challenge in 2015 whereby the theme park has a dropping number of attendances. Apart from that, the company also received more complaints over compliments regarding their products and services. This study is carried out with purposed of identifying which factor contributed the most in order to help LEGOLAND Malaysia to increase their company brand equity. The research framework links the brand awareness, brand associations, perceived quality and brand loyalty to brand equity of the company. Questionnaires been used in this research with a sample size of 400 visitors of LEGOLAND Malaysia Theme Park has been selected. The data were obtained and analysed using the Statistical Package for the Social Science (SPSS). The results reveal that brand awareness, perceived quality and brand loyalty have a significant relationship to brand equity. However, brand associations happen to not have a relationship with brand equity. The result also reveals that brand loyalty is the factor that influence brand equity the most.